Business of the heart : religion and emotion in the nineteenth century - Corrigan, John, 1952- (Berkeley : University of California Press, 2002)
The 'Businessmen's Revival' was a religious revival that unfolded in the wake of the 1857 market crash among white, middle-class Protestants. Delving into the religious history of Boston in the 1850s, John Corrigan gives an imaginative and wide-ranging interpretive study of the revival's significance.
Introduction: Religion, emotion, and the double self -- The businessmen's revival -- The anxiety of Boston at mid-century -- Overexcitement, economic collapse, and the regulation of business -- Emotion, collective performance and value -- Emotional religion and the ministerial "balance-wheel" -- Men-women, and emotion -- Domestic contracts -- Clerks, apprentices, and boyculture -- Prayerful transactions -- Emotion, character, and ethnicity -- Epilogue: The meaning of the revival and its legacy -- Appendix 1. History, religion, and emotion: a historiographical survey -- Appendix 2. Emotion as heart, blood, and body -- Appendix 3. Emotion and the common sense philosophy.
Includes bibliographical references (pages 299-369) and index.
Print version record.
JSTOR
Keywords: Revivals -- Massachusetts -- Boston -- History -- 19th century; Emotions -- Religious aspects -- Christianity -- History of doctrines -- 19th century; Protestants -- Massachusetts -- Boston -- History -- 19th century; Businessmen -- Religious life -- Massachusetts -- Boston; Réveils (Religion) -- Massachusetts -- Boston -- Histoire -- 19e siècle.; Émotions -- Aspect religieux -- Christianisme -- Histoire des doctrines -- 19e siècle.; Protestants -- Massachusetts -- Boston -- Histoire -- 19e siècle.; Hommes d'affaires -- Massachusetts -- Boston -- Vie religieuse; RELIGION -- Christianity -- History; RELIGION / Christianity / General; Businessmen -- Religious life; Emotions -- Religious aspects -- Christianity -- History of doctrines; Protestants; Revivals; Massachusetts -- Boston; Opwekkingsbewegingen; Massachusetts; 1800-1899; History